Primary Distal renal tubular acidosis: case series - Halder, Soma; Ferdous, Jannatul; Tajkia, Gule; Roy, Kuntal; Amin, Syed Khairul; Rahman, M Ekhlasur; Hanif, Mohammad (Anwer Khan Modern Medical College Journal, 2021)
Primary Distal renal tubular acidosis is an infrequent tubular disorder with complex pathophysiology that present with poor growth, skeletal changes and sometimes life-threatening hypokalemia. Here we present two siblings one girl and one boy with a consanguineous parents presented with polyuria, polydipsia, failure to thrive and skeletal deformity. Both cases showed non-anion gap metabolic acidosis with alkaline urine and the younger brother had periodic paralysis due to hypokalemia. After diagnosis and treatment they showed good response with alkali therapy. AKMMC J 2022; 13(1) : 56-59